Petroleum Engineering as a (still) promising career in geosciences? an empirical example in Northeastern Mexico - Chacón Baca, Elizabeth; Briones Carrillo, Jorge Alberto; Aguilar Madera, Carlos Gilberto; Barros Galvis, Nelson E.; Méndez Delgado, Sóstenes (Macrothink Institute, 2017)
More than ever, it is the time to increase the number of engineering students applying to geosciences in order to satisfy the growing national challenges and administrate our natural resources in a responsible and sustainable manner. This work analyzes the petroleum engineer career at the UANL through an 8 years experience in order to critically evaluate the current academic profile that petroleum engineers need within a global and shared world. This brief appraisal also presents an updated revision of all certified academic programs offering the petroleum engineering career in Mexico. At the same time, this work also proposes a modest but realistic academic modality for this particular career to better fulfill the actual academic and industrial demands on this area. Adjusting the academic geoscience workforce implies a redefinition of curricular programs, values and competences for this career in a synergic action with government policies and public and private employees worldwide. Certainly, the change should be the driving force to design modern up to date professional profiles and better oil professionals with a global perspective to take on alternative development.